LncRNA GAPLINC Promotes Renal Cell Cancer Tumorigenesis by Targeting the miR-135b-5p/CSF1 Axis - Wang, Siyuan; Yang, Xiaorong; Xie, Wenjie; Fu, Shengqiang; Chen, Qiang; Li, Zhilong; Zhang, Zhicheng; Sun, Ting; Gong, Binbin; Ma, Ming (Frontiers in Oncology, 2021)
Background Long noncoding RNAs (lncRNAs) are closely related to the occurrence and development of cancer. Gastric adenocarcinoma-associated, positive CD44 regulator, long intergenic noncoding RNA (GAPLINC) is a recently identified lncRNA that can actively participate in the tumorigenesis of various cancers. Here, we investigated the functional roles and mechanism of GAPLINC in renal cell carcinoma (RCC) development. Methods Differentially expressed lncRNAs between RCC tissues and normal kidney tissues were detected by using a microarray technique. RNA sequencing was applied to explore the mRNA expression profile changes after GAPLINC silencing. After gain- and loss-of-function approaches were implemented, the effect of GAPLINC on RCC in vitro and in vivo was assessed by cell proliferation and migration assays. Moreover, rescue experiments and luciferase reporter assays were used to study the interactions between GAPLINC, miR-135b-5p and CSF1. Results GAPLINC was significantly upregulated in RCC tissues and cell lines and was associated with a poor prognosis in RCC patients. Knockdown of GAPLINC repressed RCC growth in vitro and in vivo, while overexpression of GAPLINC exhibited the opposite effect. Mechanistically, we found that GAPLINC upregulates oncogene CSF1 expression by acting as a sponge of miR-135b-5p. Conclusion Taken together, our results suggest that GAPLINC is a novel prognostic marker and molecular therapeutic target for RCC.